Endovascular Intervention Beneficial in Pooled Analysis of MR CLEAN and IMS III. Issue 2 (11th March 2015) - Zarifyan, Alla
A pooled analysis of MR CLEAN and IMS III trial data from the patient subgroup with National Institutes of Health Stroke Scale score ≥ 20 demonstrated the benefit of endovascular therapy in addition to intravenous tissue plasminogen activator treatment in patients presenting with severe stroke.